Membangun Kesadaran Hukum Untuk Melawan Intoleransi Berdampak Bullying - Sinaga, Roulinta Yesvery; Kuahaty, Sarah Selfina; Dyastuti, Risqi Mumpuni (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Legal awareness among teenagers remains low, causing a lack of understanding about the legal consequences of bullying. Bullying often stems from intolerance towards cultural, religious, and gender differences, which can lead to physical and verbal violence in educational settings. Therefore, legal socialization is necessary to prevent intolerance from resulting in bullying and to improve the quality of education.Purposes of Devotion: This community service aims to enhance legal awareness and tolerance among students at SMP Negeri 7 Ambon to prevent bullying and create a safe and inclusive school environment. Method of Devotion: The legal socialization activity at SMP Negeri 7 Ambon involves lectures by the presenter, interspersed with interactive games to increase student engagement. After the presentation, a Q&A session is held, concluding with the writing and recitation of personal commitments to reject bullying and prioritize tolerance in daily life.Results of the Devotion: The activity led to an increased understanding among students about intolerance and bullying and their impacts. Students learned about the differences between intolerance and bullying and the importance of legal awareness. Through lectures, interactive games, Q&A, and personal commitments, students gained a better understanding of how to avoid intolerance and bullying and how to report such cases. This education reinforced tolerance and provided guidance on legal protection and preventive measures.